Gait strategies for individuals with knee osteoarthritis when transitioning between floor and stair walking - Chai, Yatai; Chen, Jian; Hou, Meijin; Zheng, Jiaqi; Liu, Lu; Chen, Yongkang; Fu, Shengxing; Ma, Ye; Hong, Tiansheng; Wang, Xiangbin (Frontiers in Physiology, 2023)
Objective: Individuals with knee osteoarthritis (OA) are at higher risk for falls during transitions between floor and stair walking due to their reduced lower extremity function. However, the adjust gait characteristics of knee OA subjects for dealing with stair transitions have not been explored. We aimed to investigate gait strategies in individuals with knee OA compared to age-matched individuals without knee OA during the transition between walking on floor and stairs. Method: Gait of 30 individuals with knee OA and 30 individuals without knee OA during floor-to-stair and stair-to-floor walking transitions were accessed using a 3D motion capture system. Foot-tread clearance (FC), and angles of lower extremity joints and trunk at FC timepoint were analyzed by using biomechanical software (Visual 3D). Results: No statistical difference was detected in vertical FC and horizontal FC comparison between the two groups. Subjects with knee OA showed smaller ankle dorsiflexion (P = 0.01), greater hip flexion (P = 0.02) and trunk lateral tilt (P = 0.02) than the control group during the stair ascent transition. Moreover, trunk lateral tilt to the support side (P = 0.003) and pelvic rotation (P = 0.03) increased, while hip abduction of the swing leg (P = 0.03) decreased during the stair descent transition in individuals with knee OA. Conclusion: Increased trunk lateral tilt and altered angle of hip may be a strategy utilized by individuals with knee OA to increase the foot clearance ability and compensate for the disease-related loss of lower extremity strength, range of motion, and balance. However, compensatory manifestations, such as the increased lateral tilt of the trunk and movement of the gravity center may enhance the risk of falls and result in more abnormal knee joint loading.